The Economics of "Crossing Over": Examining the Link between Correctional Officer Pay and Guard–Inmate Boundary Violations. Issue 1 (2nd January 2016) - Worley, Robert M.; Worley, Vidisha Barua
ABSTRACT: This study seeks to ascertain why some correctional officers engage in boundary violations with inmates in spite of the presence of strong organizational cultural norms which discourage familiarity between staff and offenders. Using an alternate version of Blau and Blau's relative deprivation theory to guide in the interpretation of our analyses, we conclude that poor pay, perceptions of boundary violations by other officers, and lack of family support, the economics, lead some officers to have a lack of pride in their work and profession, thus, triggering their closeness to inmates across the sacrosanct border, resulting in the crossing over.